The American crisis. : Let God, and the world judge between us (Printed and sold by Eben. Watson., 1775)
Broadside in support of the colonies' and the Continental Congress' positions regarding Great Britain. The document was addressed to Great Britain citizens and the general world, retelling the battle of Lexington in defense of the American position.